Religious Moderation Discourses on Digital Platforms: Upholding Diversity, Rejecting Violence, and Embracing Local Wisdom - Handayani, Rizqi; Alfida, Alfida (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University (UIN) Jakarta, 2025)
This research examines the dissemination of religious moderation discourses through digital platforms, particularly YouTube, by analyzing lectures from two moderate dai, Gus Baha and Adi Hidayat. In light of social change and the evolution of digital media, the study aims to identify the values of religious moderation reflected in their messages. Key research questions address the various da’wah approaches utilized on YouTube and how these pillars such as commitment to national unity, respect for diversity, rejection of violence, and openness to local wisdom are communicated to audiences. Employing a qualitative approach with content analysis, the study selects lecture videos through purposive sampling based on view count and thematic relevance. The findings reveal that both Gus Baha and Adi Hidayat effectively use digital platforms to convey moderation messages, albeit through different strategies. Gus Baha focuses on cultural narratives familiar to the community, while Adi Hidayat employs a scientific, structured approach rooted in religious texts. The analysis indicates that YouTube serves not only as a channel for disseminating moderate religious information but also plays a critical role in preventing radicalization by providing inclusive content. In conclusion, this study offers contribution to digital literacy policy by highlighting the role of digital media in enhancing religious moderation in Indonesia amidst complex information flows and underscores the importance of digital literacy in amplifying the positive impact of moderation messages online.